2012
DOI: 10.1089/scd.2011.0206
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Sonic Hedgehog During Cell Proliferation in the Human Cerebellum

Abstract: The regulation of cell proliferation in the external granular layer (EGL) of the developing cerebellum is important for its normal patterning. An important signal that regulates EGL cell proliferation is Sonic hedgehog (Shh). Shh is secreted by the Purkinje cells (PC) and has a mitogenic effect on the granule cell precursors of the EGL. Deregulation of Shh signaling has been associated with abnormal development, and been implicated in medulloblastomas, which are tumors that arise from the cerebellum. Given the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 35 publications
4
49
0
Order By: Relevance
“…Body mass was reduced 19% in female mice and 23% in male Atg5 ShhCre mice compared with WT littermates at this age (female mice: P = 0.0013 [n = 6-8]; male mice: P = 0.0005 [n = 5-10]) ( Figure E3F). These phenotypes, which are consistent with the reported expression pattern of Shh in lung, neural, and intestinal epithelial cells (29)(30)(31), precluded analyses of animals older than 16 months in this study.…”
Section: Analyses Of Mice In Which Atg5supporting
confidence: 74%
“…Body mass was reduced 19% in female mice and 23% in male Atg5 ShhCre mice compared with WT littermates at this age (female mice: P = 0.0013 [n = 6-8]; male mice: P = 0.0005 [n = 5-10]) ( Figure E3F). These phenotypes, which are consistent with the reported expression pattern of Shh in lung, neural, and intestinal epithelial cells (29)(30)(31), precluded analyses of animals older than 16 months in this study.…”
Section: Analyses Of Mice In Which Atg5supporting
confidence: 74%
“…Although we were not able to detect the expression of SHH in PCs before 17 gw, we observed that GCPs expressed GLI1 at all stages analyzed (Fig. 3B), suggesting that an additional source of SHH might exist before 17 gw (32,33). However, SHH mRNA expression detected in the PCs from 17 gw coincides with a peak in GCP proliferation (Figs.…”
Section: Gcp Proliferation Is Similar In Cerebellar Vermis and Hemispmentioning
confidence: 81%
“…Mid-sagittal cryo-sections of the cerebellum at 11 microns were taken. H&E staining and immunohistochemistry were performed as described previously 38 . Briefly, cryosections were incubated at room temperature for 1 hour after which they were subjected to heat-mediated antigen retrieval.…”
Section: Methodsmentioning
confidence: 99%